Gender differences and self-regulated learning: The effect of prior academic achievement - Torrano, Fermín; Soria, María (Revista Complutense de Educación, 2017)
In the last two decades self-regulated learning has become a current focus for research, and one of the essential axes for educational practice. In this context this paper´s objective is to analyze gender differences in academic and strategies use, and what occurred when we control academic achievement. The sample is formed by N=374 students 13-14 years old. Motivational scales of the Patterns of Adaptive Learning Scales (PALS) focusing on student (contextual and personal goals, selfefficacy beliefs and self-handicapping strategies) and MSLQ cognitive scales were used. The results show significant differences between boys and girls in all motivational scales and considered strategies, except on mastery goals and elaboration. However, to control the effect of prior performance, it was confirmed how some of these differences disappeared. As a possible explanation, highlights the need to control prior achievement, and to analyze carefully the stereotypes developed by each gender and bias in the response to questionnaires according to sex.